Ant social foraging strategies along a Neotropical gradient of urbanization - Wesley Dáttilo (Nature Portfolio, 2021)
Abstract During the last decades, urbanization has been highlighted as one of the main causes of biodiversity loss worldwide. Among organisms commonly associated with urban environments, ants occupy urbanized green areas and can live both inside and around human settlements. However, despite the increasing number of studies on the ecological dynamics of ant species developed mainly in temperate urban ecosystems, there is still little knowledge about the behavioral strategies that allow ant species to live and even thrive within cities. In this study, we evaluated the role of urbanization in shaping ant communities, including their social foraging, considering built cover as a gradually changing variable that describes an urban gradient. Specifically, we assessed whether species richness, composition, and the proportion of exotic ant species are related to an urban gradient in a medium-sized Neotropical city immersed in a cloud forest context in Mexico. Moreover, we evaluated the social foraging strategies that could promote ant species coexistence in an urban environment. In general, and contrary to our hypothesis, we found no evidence that the built cover gradient affected the richness, composition, or proportion of exotic ant species foraging on food resources, indicating a filtering and simplification of ant communities given by urbanization. Moreover, we show for the first time that urban ant species exhibited a “discovery-defense strategy”, whereby the ant species with the greatest capacity to discover new food resources were those that showed the greatest ability to monopolize it after 120 min of observation, regardless of the type of resource (i.e., tuna or honey bait). Our findings have a direct impact on the knowledge about how urbanization shapes ant communities and behavior, by showing the foraging strategies of ant species that feed on similar food resources present that allows them to coexist in urban environments.